Ultra baixo coeficiente de atrito no deslizamento de Si3N4 Al2O3 em água: estudo ab initio do running-in - Balarini Junior, Roberto (2013)
This work is a tribological investigation involving the ceramic pair composed by balls of silicon nitride (Si3N4) sliding against disks of aluminum oxide (Al2O3) under water. A total of ten tests were conducted in order to reproduce the phenomenon of Ultra Low Friction Coefficient (ULFC) in laboratory, which is characterized by obtaining values of friction coefficient (μ) below of 0,01 in the steady state. Once reached these values, the main objective of this study was to investigate the running-in period by a series of analyses in relation to the behavior of the friction coefficient during the running-in period, including correlations with some variables such as surface roughness, axial parallelism errors, ions formed during the sliding and wear of samples. For this reason, the curves of friction coefficient versus time were expanded for some predetermined intervals and the behavior of μ for each one of these intervals was investigated and compared between themselves, and the oscillatory behavior of the friction coefficient was inserted into the analysis of the running-in period. In general, it was concluded that higher values of surface roughness resulted in longer periods of running-in and that there is a trend of increasing wear with increasing time of transition. For all tests, the wear rate of the silicon nitride balls was higher than alumina disks. In addition, by comparing the measure of the sum of the roughness of the worn surfaces with minimum thickness of the lubricant film, the present work confirms the hypothesis that it is necessary a mixed lubrication (hydrodynamic combined with boundary) to obtain the regime of ULFC and for effective lubrication expected mode it is estimated that is required an ions concentration of silicon (Si) higher than 1.3 mg/l approximately. This amount of ions Si is supposed to be the minimum necessary for the formation of a silica layer enable to confer the boundary lubrication participation for obtaining the ULFC